PENGARUH PENGGUNAAN MINUMAN KERAS PADA KEHIDUPAN REMAJA DI DESA KALI KECAMATAN PINELENG KABUPATEN MINAHASA - Rori, Peggy Lusita Patria (HOLISTIK, Journal Of Social and Culture, 2015)
Liquor or called also alcoholic beverages is a drink containing a substance ethanol. Ethanol himself is the substances or ingredients that when consumed would reduce the awareness of it has its consumers (drunk). Liquor may destroy the thought processes and make somebody unconscious or acting according to volition.The assumption that many teenagers with the drink liquor their confidence increased from a timid to be brave and all problems can be handled with drink of liquor.The opportunity to get liquor very easy especially in desa Kali. The seller does not have formal permission to sell liquor. Because most liquor in desa Kali produced by local people.The dominant factor that causes behavior wassail the youth is the first individual factors, curiosity every individual, especially for teenagers by which either are first of all is want to try and new things and then into the causes of consume liquor. Curiosity toward liquor who they regard as something new and then try it, want to know that that is due to finally become hooked.A drinker liquor impact teen behavior on the psychological state that is inclined to want to consume liquor consistently (addiction), to the physical condition is associated with their health conditions, and in the surrounding environment the things that relating to a response from his family environment, the group and the surrounding community.Keywords : Liquor, teenagers, drunk